Development of a heat stress-related symptoms prediction model among steel mill workers in East Java Indonesia - Nurhartonosuro, Imam Munajat (2022)
Due to a tropical region and hot workplace environment, workers at steel mills in East Java, Indonesia has high susceptibility to heat stress exposure. The study aims to determine heat stress affecting factors and heat stress-related symptoms that workers can experience due to the exposure to workload and hot environment at steel mill. The total respondents involved in data collection were 119 operators exposed to hot workplace in three different mill locations, i.e., Surabaya, Sidoarjo, and Gresik, East Java, Indonesia. The study consists of two phases, in which Phase 1 was the cross-sectional study and data collection via observation and questionnaires distribution to estimate variables of heart stress, of individual risk factors, acute health score symptoms, environmental factors (WBGTin, relative humidity, clothing and metabolic workload) and physiological changes (body core temperature, heart rate, and blood pressure), and workers’ thermal perception. All the data were analyzed to establish the correlation between heat stress factors and heat stress-related symptoms. In Phase 2 as qualitative research, it compared the output of heat stress related symptoms with the in-depth interview with some expert and informants selected from the sample mills. The study results found that the heat stress related symptoms the workers most experienced during working were profuse sweating; fatigue; fainting; dizziness; seizures; heat rash and heat stroke. The results show that respondents from Steel Mill B experienced more symptoms of health problems than the other two mills. Most workers in three mills experienced severe thirst and excessive sweating due to hot environment. In three mills, lowest humidex value of 41, while the highest of 52.1, and the average humidity of 58.03%, and the lowest temperature was at Steel Mill C (28.54oC). On the other hand, the highest temperature was at Steel Mill B (47.92 oC). The physiological changes, such as body core temperature, heart rate, and blood pressure were the highest during working and the lowest after working. The variables WBGT, relative humidity, blood pressure diastolic, body core temperature and heart rate are predictors or determinants of heat related symptoms with a coefficient of determination of 61.4%., while 38.6% is explained by other variables that are not used in the model. WBGT positively affects the heat stress related symptoms, humidity, positively, affects the heat stress related symptoms but non-significant effect on heat stress related symptoms. Systolic, positively affects but non-significant effect on heat stress related symptoms, while diastolic, negatively, affects the heat stress-related symptoms but non-significant effect, body core temperature positively and significantly affects heat stress-related symptoms. Heat rate positively and significantly affects the heat stress related symptoms. Based on the principal component analysis (PCA) result, there are three variables that have a strong correlation (> 0.5) with factor 1, namely WBGT, relative humidity and body core temperature. The three variables are then grouped into factor 1; Factor 2. Two variables have a strong correlation with factor 2, namely blood pressure systolic and diastolic. The two variables are then grouped into factor 2. The qualitative data was gathered from 15 informants (5 informants per company) through in-depth interview, where blood pressure was perceived in association with heart rate. There were 15 informants who familiar with the terminology of blood pressure in association with heart rate. This finding is in line with the quantitative results, that heat related symptoms predictive index have positive relationship to heat stress symptoms. This finding is in line with the quantitative results, that room temperature (WBGT and body core temperature) positively affect heat related symptoms predictive index, blood pressure (heart rate), room temperature (WBGT – body rate) have relationship to heat stress- related symptoms. There were significant differences (significance value 0.00 < 0.05) in the WBGT index of the three mills. Based on the Tukey test results, there was a significant difference in the Humidex index only between Steel Mill B and Steel Mill C (Sig 0.035 <0.05). There are significant differences in the AHS index between the three mills, except between Steel Mill B and Steel Mill C (Sig 0.857 > 0.05). There were significant differences in the thermal comfort perception between the three mills, except between Steel Mill A and Steel Mill C (Sig 0.753 > 0.05). There were significant physiological changes (significance value 0.000 < 0.05) from the three mills were only found in the variable of body core temperature. The comparison test results revealed that there were significant differences in workload (significance value 0.048 <0.05) from the three mills. The physiological factor (body core temperature and heart rate) and environmental factor (Wet Bulb Global Temperature – Room Temperature) positively and significantly proven as predictor of heat stress-related symptoms prediction model. It was confirmed by qualitative data as being perceived by the respondents.